High-performance liquid chromatographic separation and identification of polyphenolic compounds from the infusion of Davilla elliptica St. Hill - Rodrigues, Clenilson M. [UNESP]; Rinaldo, Daniel [UNESP]; Sannomiya, Miriam [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Montoro, Paola; Piacente, Sonia; Pizza, Cosimo; Vilegas, Wagner [UNESP] (John Wiley & Sons Ltd, 2008)
The isolation of polyphenolic compounds from an infusion of the Brazilian plant Davilla elliptica (Dilleniaceae), used as tea by virtue of its digestive properties, is described. An improved preparative HPLC method was used in order to isolate pure polyphenols from the complex mixture. Liquid-liquid extraction and solid-phase extraction were employed to minimise the interference of polymeric compounds and to provide an enriched fraction of the compounds of interest. The identification of the isolated compounds was performed using analytical HPLC as well as direct injection electrospray ionisation ion trap tandem mass spectrometry (ESI-IT-MS/MS). The high flavonoid content suggests that D. elliptica may be a promising source of compounds to produce natural phytomedicines. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: preparative HPLC; solid-phase extraction; infusion analysis; flavonoids; Davilla elliptica; Dilleniaceac